2011
DOI: 10.1136/heartjnl-2011-300920b.47
|View full text |Cite
|
Sign up to set email alerts
|

47 Endothelial progenitor cells contribute to vascular repair in the ischaemic retina

Abstract: Numerous studies suggest that endothelial progenitor cells (EPCs) re-vascularise ischaemic tissues and recent clinical trials have highlighted the feasibility, safety and potential therapeutic benefit of an EPC-based cytotherapy for myocardial infarction. However there is still discrepancy about the extent to which these cells incorporate into the vasculature and the level to which they restore functionality to damaged tissue. These controversies are caused by an imprecise EPC definition as many different cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A N U S C R I P T be used immediately or cryopreserved for future use. Since, OECs display limited replicative potential in vivo, they are recognised as safe therapeutic components [106] and since they are able to detect and home into host endothelium in vivo, they are also recognised as efficacious therapeutic components. Indeed, human OECs administered into a murine model of retinal ischaemia by intra-vitreous injection have been shown to incorporate into the resident vasculature within 72 h of injection where they increase normal retinal vasculature, decrease avascular areas and suppress pathological pre-retinal neovascularisation [105].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…A N U S C R I P T be used immediately or cryopreserved for future use. Since, OECs display limited replicative potential in vivo, they are recognised as safe therapeutic components [106] and since they are able to detect and home into host endothelium in vivo, they are also recognised as efficacious therapeutic components. Indeed, human OECs administered into a murine model of retinal ischaemia by intra-vitreous injection have been shown to incorporate into the resident vasculature within 72 h of injection where they increase normal retinal vasculature, decrease avascular areas and suppress pathological pre-retinal neovascularisation [105].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…These controversies are caused by an imprecise EPC definition as many different cell populations are collectively referred to as EPCs. Recently, Medina and colleagues [ 82 ] described a distinct EPC population named outgrowth endothelial cells (OECs). OECs were isolated from adult human peripheral blood and grown on collagen substrate.…”
Section: Potential Sources Of Stem Cells For Cell Therapy In Retinal mentioning
confidence: 99%
“…This is also demonstrated in vivo , where OECs directly incorporate into resident ischemic vasculature and significantly decreased avascular areas ( P < 0.001) when compared with vehicle-injected retinas. The authors concluded that OECs have great potential as an alternative treatment for ischemic retinopathies [ 82 ].…”
Section: Potential Sources Of Stem Cells For Cell Therapy In Retinal mentioning
confidence: 99%
“…Using this in vitro approach, at least two distinct types of "EPCs" with different angiogenic properties have been identified: "early EPCs" (or myeloid angiogenic cells [MACs]) and "late EPCs" (or endothelial colony-forming cells [ECFCs]) [24][25][26][27]. While "early EPCs" represent hematopoietic cells that support endothelial repair and regeneration in injured vessels through largely proangiogenic paracrine mechanisms [15,28,29], "late EPCs " (ECFCs) are committed to an endothelial lineage fate and have significant proliferative and de novo vasculogenic potential [30][31][32][33][34]. Only "late EPCs" (ECFCs) can display in vitro clonogenic potential and in vivo vessel-forming potential [30][31][32][33][34]; functional capacities that "early" EPCs lack.…”
Section: Vascular Endothelial Stem and Progenitor Cellsmentioning
confidence: 99%
“…As noted above, accumulating evidence indicates that many of the putative circulating marrow-derived EPCs contribute to neovascularization by a paracrine manner and fail to display vasculogenic activity by themselves. Rather, this property is reserved for circulating ECFCs, a rare population of viable endothelial cells with colony-forming cell ability in the blood stream [15,28,33,36,66]. Cord blood and peripheral blood ECFCs are well-known circulating ECFCs and can be derived from blood mononuclear cells and possess robust proliferative potential and capacity to form new blood vessels in vitro and in vivo [2,31,32,37,67].…”
Section: Circulating Endothelial Stem Cells (Circulating Ecfcs)mentioning
confidence: 99%